Neuroprotective Effects of Quercetin on Ischemic Stroke: A Literature Review - Zhang, Leilei; Ma, Jingying; Yang, Fan; Li, Sishi; Ma, Wangran; Chang, Xiang; Yang, Lin (Frontiers in Pharmacology, 2022)
Ischemic stroke (IS) is a disease characterized by high recurrence and disability, but its therapies is very limited. For the treatment of acute IS, intravenous thrombolysis is the only method that is effective, but it has a clear treatment timeframe limitation. Quercetin, a flavonoid widely found in vegetables and fruits, has been shown to have good neuroprotective effects in preclinical studies of central nervous system diseases. After ischemia, quercetin has a amount of effects on the brain including reduced infarct size and edema, anti-oxidative stress, anti-apoptosis, increasing autophagy and neuroprotection. The article focuses on the therapeutic potential of quercetin over IS brain injury, with an emphasis on its source, physicochemical properties, and improvement of ischemic brain injury.